2007
DOI: 10.1103/physrevlett.98.203902
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of Modulation Instability and Optical Spatial Soliton Arrays in Soft Condensed Matter

Abstract: In this Letter we report observations of optically induced self-organization of colloidal arrays in the presence of un-patterned counter-propagating evanescent waves. The colloidal arrays formed along the laser propagation-axis are shown to be linked to the break-up of the incident field into optical spatial solitons, the lateral spacing of the arrays being related to modulation instability of the soft condensed matter system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
76
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 25 publications
3
76
0
Order By: Relevance
“…For four-wave mixing experiments this Kerr approximation is acceptable if the incident optical intensities are controlled such that n 2K I Ӷ 1. Reece et al, 2007;Lee et al, 2009͒ indicated that the exponential nonlinearity model seems to have the lowest correlation with experiments, followed by the artificial Kerr medium approach ͑Lee et al, 2009͒. Theoretical nonideal gas based model including the effects of the limited compressibility of the particle suspension agreed well with the experimental results.…”
Section: ͑53͒supporting
confidence: 71%
See 1 more Smart Citation
“…For four-wave mixing experiments this Kerr approximation is acceptable if the incident optical intensities are controlled such that n 2K I Ӷ 1. Reece et al, 2007;Lee et al, 2009͒ indicated that the exponential nonlinearity model seems to have the lowest correlation with experiments, followed by the artificial Kerr medium approach ͑Lee et al, 2009͒. Theoretical nonideal gas based model including the effects of the limited compressibility of the particle suspension agreed well with the experimental results.…”
Section: ͑53͒supporting
confidence: 71%
“…Bright-field imaging also confirms the presence of ordered colloids in regions of high intensity. From Reece et al, 2007. mediated particle-particle interactions observed in optical binding, particularly in light of the recent reports of two-dimensional checkerboardlike array formation in a trapping geometry similar to the one described above. An interpretation of the behavior of optically bound colloidal systems from a nonlinear systems approach may provide further insights into the observed pattern formation for such lateral binding.…”
Section: ͑53͒mentioning
confidence: 99%
“…As the lattice is self-organized and not externally imposed, it is not rigid but can have dynamics leading to the possibility to study the propagation of coupled light-density perturbations, correlations of fluctuations in the light and density modes, and, in presence of atomic coherence, corresponding features in quantum transport. The mechanism of self-structuring with optical feedback described here is expected to apply also to the electron density in a plasma in the presence of ponderomotive forces 28 , to 'soft matter' formed from dielectric beads 22,23 , and deformable membranes 29 . Beside periodic patterns, one emerging feature suggested by theoretical simulations is the possibility of localized, soliton-like, density-light structures (single or multiple holes in the density), which can be set and erased by external control pulses and sustained by homogeneous driving only 30 .…”
mentioning
confidence: 99%
“…The crucial new ingredient in cold atoms is the existence of macroscopic matter transport processes due to dipole forces, leading to density self-organization without the need for an intrinsic optical nonlinearity (first experimental clues of such an effect in a very low aspect ratio situation were obtained in 9 ). Compared to soft matter systems [21][22][23] cold atoms have the advantage that the dynamics can be studied without viscous damping of motion, allowing for a dissipation free evolution with a Hamiltonian description of the system. It is possible, however, to introduce dissipation in a controlled way, if desired, via optical molasses 6,9,13,14 .…”
mentioning
confidence: 99%
“…Recently, there has been an increasing interest in light controlled motion of microorganisms and their hosting flows [6,7], but these controls are based on phototaxis in bacterial suspensions rather than optical nonlinearity. To efficiently propagate light through highly scattering media, it is important to study the nonlinear optical properties of soft-matter systems [8][9][10][11][12]. In particular, an optical nonlinearity can lead to stable low-loss propagation and deep penetration of light in scattering media such as nanoparticle suspensions, which could be employed to noninvasively initiate and control chemical or mesoscopic kinetic processes, as well as to study living organisms with high-resolution depth-resolved optical imaging [13,14].…”
mentioning
confidence: 99%